1981
DOI: 10.1017/s0025727300034876
|View full text |Cite
|
Sign up to set email alerts
|

Glanders: medicine and veterinary medicine in common pursuit of a contagious disease

Abstract: TODAY, GLANDERS is a disease rarely heard of in Western Europe, Britain, and North America; but a hundred years ago the annual total of cases of glanders in the horse, published by the Board of Agriculture, exceeded 2,000,1 and British veterinarians were all too familiar with the disease. Moreover, transmission to man took place with distressing regularity, and the outcome was nearly always fatal.2 In 1908, William Hunting, Chief Veterinary Inspector to the London County Council, wrote: "Glanders in man is suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
30
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 3 publications
0
30
0
1
Order By: Relevance
“…Primarily a disease of solipeds, glanders is generally confined to equines (horses, mules and donkeys) [1,2]. Glanders in solipeds presents as a chronic or as an acute disease.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Primarily a disease of solipeds, glanders is generally confined to equines (horses, mules and donkeys) [1,2]. Glanders in solipeds presents as a chronic or as an acute disease.…”
Section: Introductionmentioning
confidence: 99%
“…The chronic form occurs either as a pulmonary disease, an upper respiratory disease, or a cutaneous disease. The symptoms of the acute form of the disease include high temperature, depression, shortness of breath, diarrhea, and rapid weight loss with mortality [1,2]. Death may occur after a few weeks from an acute infection, whereas the chronic form of glanders may persist for years and may end in death.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…B. mallei causes the zoonotic disease glanders, which mainly affects horses. B. mallei can also infect humans, an infection that is almost invariably fatal if untreated (19). The gram-negative soil saprophyte B. thailandensis is nonpathogenic in Syrian hamster models of infection (2) and was previously classified as an arabinose positive (Ara ϩ ) nonpathogenic variant of B. pseudomallei (3).…”
mentioning
confidence: 99%
“…In this study, we identified the O-PS biosynthetic gene cluster from B. mallei ATCC 23344 and subsequently characterized the molecular structure of the O-PS produced by this organism.Burkholderia mallei is a gram-negative bacterium responsible for a disease known as glanders in solipeds and occasionally in humans (3,8,13). The factors involved in the pathogenesis of B. mallei infection remain relatively poorly defined at the molecular level.…”
mentioning
confidence: 99%